ANALISIS PIDANA TAMBAHAN KEBIRI KIMIA DALAM UNDANGUNDANG NOMOR 17 TAHUN 2016 TENTANG PENETAPAN PERATURAN PEMERINTAH PENGGANTI UNDANGUNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK BERDASARKAN PERSPEKTIF HAK ASASI MANUSIA - Grace Tiur Esterella Silalahi; Mukhlis R; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Indonesian Criminal Law only recognizes two types of crimes, namely basic crimes andadditional crimes. Chemical castration is included in additional penalties in Indonesia which areregulated in Law Number 17 of 2016 concerning Stipulation of Government Regulations in Lieu ofLaw Number 23 of 2002 concerning Child Protection which provides weighting and additionalcriminal penalties for perpetrators of sexual violence against children as regulated in article 81paragraph 7 that "The perpetrators as intended in paragraphs (4) and (5) may be subject to chemicalcastration and the installation of electronic detectors. For example, the case of Muhammad Aris (21years) sexually abused 9 children in Modjokerto. Chemical castration has not been carried out becauseof rejection from the National Human Rights Commission (Komnas HAM) expressing its disapprovalbecause it is contrary to human rights as written in the 1945 Constitution of the Republic of IndonesiaArticle 28G paragraph 2 which reads "Everyone has the right to free from torture and treatmentdegrading human dignity ”. The purpose of this study is to determine additional criminal regulationsfor chemical castration in several countries, to find out additional criminal penalties for chemicalcastration in the perspective of human rights in Indonesia, and to find out normative alternativesolutions to the problem of chemical castration in Indonesia which are regulated in GovernmentRegulation Number 70 of 2020 concerning Tata How to Perform Chemical Castration.In this study the author focuses on normative legal research on comparison of law with thedata sources used are secondary data and data collection techniques for normative legal research usethe literature review method and use descriptive analysis which provides a description of the object ofresearch based on data obtained from the subject under study.From the research results, it can be concluded that there are several countries in the world thathave imposed chemical castration punishment but in practice it is still not effective. The imposition ofadditional chemical castration punishment aims to reduce the number of sexual crimes and provide adeterrent effect on perpetrators of sexual crimes against children. However, it is contrary to humanrights as written in the 1945 Constitution Article 28G paragraph 2. By providing additionalpunishment for chemical castration, imposing maximum imprisonment, fines and rehabilitation as wellas providing counseling guidance while in a correctional institution and conducting supervision whenthe convict is free. The author's suggestion is to all countries in the world that have imposed physicaland chemical castration penalties to be more selective in diagnosing what crimes the castrationpunishment can apply to. Also, law enforcers in imposing castration penalties should consider theperpetrators' human rights more and implement alternative solutions that have been made.Keywords: Additional Crime-Chemical Castration-Human Rights